ARTIFICIAL INTELLIGENCE IN THE RETAIL SECTOR: MARKET AND BUSINESS MODEL TRANSFORMATION - Ibrahim Sagio; Ignatius Septo Pramesworo; Silvia Ekasari (Adisam Publisher, 2025)
In the dynamic landscape of the retail industry, Artificial Intelligence (AI) has become an important catalyst for transformation. The study in this research used a literature review. The research findings show that AI contributes to the personalization of the customer experience, with machine learning algorithms offering personalized product recommendations, increasing engagement, and stimulating sales. In terms of inventory and supply chain management, AI helps optimize stock through accurate forecasting, reduce wastage, and adapt procurement to changing market demands. Automated cashier operations and the use of chatbots effectively reduce waiting times and improve customer service quality. Analysis of the rapid development of consumer behavior through AI allows for more responsive and aspiring marketing strategies.